PENGARUH PUNISHMENT DAN REWARD TERHADAP KINERJA KARYAWAN DALAM MENYELESAIKAN TARGET PERUSAHAAN PADA PT. AGRICINAL BENGKULU UTARA - Melia, Sindia Okta; Ekowati, Sri (UM. Bengkulu, 2025)
The purpose of this study is to analyze the influence of punishment and reward on employee performance at PT. North Bengkulu Agricinal. The dependent variable in this study is employee performance (Y). while the independent variables are reward (X1) and punisment (X2). The population used in this study is employees of PT. Agricinal North Bengkulu with a total of 112 employees, while the purposive sampling technique and sample were obtained from 112 respondents. The research methods used are descriptive and qualitative methods. For the data analysis method, the multiple linear regression analysis method uses the help of the SPSS 21.0 program. The results of the study showed that rewards had a significant positive effect and punishment had a negative and significant effect on employee performance at PT. North Bengkulu Agricinal. The magnitude of the R Square value in the reward and punishment variables affecting performance was 92.9%Keywords: Reward, Punishment and Employee Performance